De Stijl 1917-1931. (Hasselt : Provinciaal Museum, 1982)
Mondriaan, Piet ; van 't Hoff, Robert ; van der Leck, Bart ; Theo van Doesburg ; Huszar, Vilmos ; Oud, J.J.P. ; Wils, Jan ; Vantongerloo, George ; Rietveld, G. Th. ; Richter, Hans ; Lissitsky, El ; van Eesteren, C. ; Schröder-Schräder, T. ; Schwitters, Kurt ; Kiesler, Frederik ; Domela, Cesar ; Vordemberge Gildewart ; Arp, Hans ; Täuber, Sophie
De Stijl 1917-1931, Provinciaal Museum, Hasselt, 24.4- 13.6.1982
boek